PENGARUH IMPLEMENTASI SISTEM INFORMASI MANAJEMENAN DAERAH DAN KEGIATAN PENGENDALIAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (SURVEY PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) KOTA PALU) - Erviana, Erviana (Katalogis, 2017)
The research is  aimed to explore and analyze: 1) The implementation of local management information system and controlling activities; 2)  Significant influence of  local management information system implementation and controlling activities on the quality financial statements; 3) Signifacant influence of local management  information system implementation on the quality financial statements; 4)  Significant influence of  controlling activities on the quality financial statements.  The test result find that: a) The implementation of local management information system and controlling activities have significancy influence on the quality financial statements. b) The implementation of local management information system has positive but insignificant influence on the quality financial statements. This is shown by coefficient regression value of 0.089 or 0,89 % with  significant value of  0,090. c) controlling activity has significant influence of the quality of financial statements with coefficient regression value of  0.190 or 19,0 % and significant value at 0,000.